The characteristics of arterial spin labeling cerebral blood flow in patients with subjective cognitive decline: The Chinese imaging, biomarkers, and lifestyle study - Li, Wenyi; Jiang, Jiwei; Zou, Xinying; Zhang, Yuan; Sun, Mengfan; Jia, Ziyan; Li, Wei; Xu, Jun (Frontiers in Neuroscience, 2022)
Objective: We aimed to characterize the potential risk factors and cerebral perfusion of patients with subjective cognitive decline (SCD). Methods: This prospective study enrolled consecutive patients from the Chinese Imaging, Biomarkers and Lifestyle (CIBL) Cohort of Alzheimer’s Disease between February 2021 and March 2022. Patients who met the SCD diagnostic criteria were categorized into the SCD group, while those without cognitive complaints or any concerns were assigned to the Healthy Control (HC) group. The demographic and clinical characteristics, and cerebral blood flow (CBF) from pseudo-continuous arterial spin labeling (pCASL) in standard cognitive regions were compared between these two groups. Multivariate analysis was performed to identify independent factors associated with SCD. Results: The frequency of family history of dementia in SCD group was higher compared with HC group (ꭓ2=5.686, P =0.029). The CBF of left hippocampus (t=-2.33, P =0.023), left parahippocampal gyrus (t=-3.04, P =0.004), left precuneus (t=-2.23, P =0.029), left middle temporal gyrus (t=-2.35, P =0.022), right parahippocampal gyrus (t=-2.43, P =0.018), and right precuneus (t=-2.31, P =0.024) in SCD group were significantly increased than those in the HC group. Multivariate logistic regression analysis revealed that the family history of dementia (OR=4.284 (1.096-16.747), p=0.036) and left parahippocampus (OR=1.361(1.006-1.840), p=0.045) were independently associated with SCD. Conclusions: This study demonstrated that the family history of dementia and the higher CBF within the left parahippocampal gyrus were independent risk factors associated with patients with SCD, which could help in early identification of the SCD and in intervening during this optimal period.